Removal of Neutral Violet Dye From Aqueous Solution by Using Psidium guajava Leaf Powder - Srinivas, Ch.; Nagamani, Ch.; Gangadhar, M.; Raja Sekhar, M. (Asian Journal of Chemistry, 2010)
Present research work deals with the bleaching of neutral violet dye have been carried out in presence of adsorbent guava leaf powder. The source used for energy is visible light. Various parameters like dosage of adsorbent, pH, concentration of neutral violet dye etc., are studied. Experiments are carried out to remove the neutral violet dye stuff by using adsorbent guava leaf powder. It is observed that the dye concentration increases with the decrease in bleaching rate. For an amount of 0.10 g at a pH value of 9 maintained of adsorbant. The bleaching rate is maximum and found to be decreasing with increasing pH and amount of adsorbent. The maximum bleaching rate is observed at the optimum time at 90 min. Neutral violet dye was removed up to 91.3 % by using adsorbant guava leaf powder.